Evaluation of the anti-acne effectiveness of Andaliman (Zanthoxylum acanthopodium DC) nanoemulgel in propionibacterium acnes-induced male wistar rats - Micella Tanessa; Chrismis Novalinda Ginting; Linda Chiuman; Masdalena; Mangatas Halomoan Parluhutan Hutagalung (Jurnal Teknologi Laboratorium)
Acne vulgaris is an inflammatory disorder of the pilosebaceous unit, characterized by lesions such as comedones, papules, pustules, nodules, and cysts. This study aimed to assess the effectiveness of Andaliman Extract Nanoemulgel (Zanthoxylum Acanthopodium DC) in treating acne lesions in male Wistar rats (Rattus Novergicus) induced with Propionibacterium acnes. This experimental involved 30 male Wistar rats aged 6-8 weeks, weighing 150-200 grams, divided into 6 groups: 1) normal, 2) negative control (P. acnes induction and base gel), 3) positive control (P. acnes induction and Mediklin TR gel), 4) Treatment 1 (P. acnes induction and 2% Nanoemulgel), 5) Treatment 2 (P. acnes induction and 3.5% Nanoemulgel), and 6) Treatment 3 (P. acnes induction and 5% Nanoemulgel). Nanoemulsion application was carried out for 10 days to evaluate the healing of acne lesions on the skin of Wistar rats. Results showed that Andaliman Extract Nanoemulgel effectively healed lesions caused by Propionibacterium acnes. In conclusion, Nanoemulgel with Andaliman fruit extract at concentrations of 2% and 5% demonstrated the highest effectiveness in anti-acne treatment.